Pengaruh Budaya Organisasi, Lingkungan Kerja dan Etos Kerja Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening pada Dinas Pendidikan Provinsi Sumatera Barat - Susanti, Tuti; Yulasmi, Yulasmi; Zefriyenni, Zefriyenni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of organizational culture, work environment, and work ethic on work motivation and employee performance, with work motivation as an intervening variable at the Education Office of West Sumatra Province. This research employed a quantitative approach using Structural Equation Modeling - Partial Least Square (SEM-PLS). A total of 98 employees participated in this study, selected through purposive sampling techniques. The results indicate that organizational culture, work environment, and work ethic significantly affect work motivation. Furthermore, organizational culture has a positive but not significant effect on employee performance, while work environment and work ethic significantly affect employee performance. Work motivation was found to have a positive but not significant effect on employee performance. Regarding mediation, the findings reveal that organizational culture significantly affects employee performance through work motivation, and work environment significantly affects employee performance through work motivation, whereas work ethic shows a positive but not significant effect on employee performance through work motivation. These findings imply that in order to improve employee performance, the organization should pay greater attention to the work environment and work ethic directly, while also optimizing the role of work motivation as a mediator between organizational culture and work environment on employee performance.